All in the Family On Community and Incommensurability - Ferguson, Kennan (Duke University Press, 2012)
Western political philosophers since Plato have used the family as a model for harmonious political and social relations. Yet, far from being an uncontentious domain for shared interests and common values, the family is often the scene of intense interpersonal conflict and disagreement. In All in the Family, the political theorist Kennan Ferguson reconsiders the family, in its varied forms, as an exemplar of democratic politics and suggests how real rather than idealized family dynamics can help us to better understand and navigate political conflict. By closely observing the attachments that arise in families despite profound disagreements and incommensurabilities, Ferguson argues, we can imagine a political engagement that accommodates radical differences without sacrificing community.